THE POSITION AND IMPLICATIONS OF TESTING MPR/S DECISIONS IN THE INDONESIAN STATE SYSTEM - Ananda, Adhe Ismail (NOMOI Law Review, 2025)
The constitutional dynamics of Indonesia have undergone rapid development, marked by four amendments to the 1945 Constitution. These dynamics have affected the authority of state institutions, including the People's Consultative Assembly (MPR) and its legal products, namely MPR Decrees (TAP MPR/S), whose hierarchy in the legislative system has evolved. This study aims to analyze the position and implications of judicial review of MPR Decrees within Indonesia’s constitutional system. A normative juridical research method is used by examining legal materials, legislation, and legal doctrines. The study finds that the status of MPR Decrees has changed significantly before and after the constitutional amendments. Before the amendments, MPR Decrees were positioned above laws but below the Constitution, whereas after the amendments, their status became uncertain due to the removal and subsequent reintroduction into the legal hierarchy. This uncertainty creates legal gaps in judicial review mechanisms, necessitating solutions such as constitutional review by the Constitutional Court, a fifth constitutional amendment, or a legislative review by the MPR itself.